Pharmacy Strategy Formulation Based on Integration of Balanced Scorecard and SWOT Analysis: A Case Study - Ahmad Suriyadi Muslim; Titik Sunarni; Tri Murti Andayani (GLOBAL HEALTH SCIENCE GROUP, 2025)
X Pharmacy Yogyakarta faces increasingly intense competition from growing competitor pharmacies in its operating area. Performance evaluation using the Balanced Scorecard (BSC) method has been conducted, but has not been comprehensively integrated with SWOT Analysis for strategic development formulation. Objective: This study aims to formulate a development strategy for X Pharmacy Yogyakarta through integration of Balanced Scorecard performance evaluation results with SWOT Analysis. This study employed a non-experimental case study design with an exploratory descriptive approach. Data were collected prospectively and retrospectively at X Pharmacy Yogyakarta during the period 2017-2020. A total of 65 patient respondents were recruited using purposive sampling for the customer perspective, and all pharmacy employees were included as respondents for the learning and growth perspective. Financial data were retrieved retrospectively for 2017-2019, while prescription data were observed prospectively over 14 working days. Data were analysed descriptively using IFAS and EFAS matrices to determine the pharmacy’s strategic position based on BSC performance evaluation covering four BSC performance evaluation showed that financial performance (GPM, NPM, ITOR) met established standards. Customer satisfaction was high, but patient growth declined. Average drug availability was 93.87% and Drug Related Problems (DRP) were still identified. Employee satisfaction and morale were high, but productivity was low. SWOT analysis yielded a total IFAS score of 2.94 and EFAS score of 2.57, with SO (Strength-Opportunity) as the primary strategy. Recommended strategies include enhanced patient-oriented pharmaceutical services, human resource development, service innovation, and drug management optimisation. Integration of BSC and SWOT analysis produced a comprehensive strategy map that can serve as a reference for X Pharmacy management in improving competitiveness and quality of pharmaceutical services.